Peran Pemikiran Konseptual Ekonomi Abu Ubaid terhadap Fungsi uang dan Relevansinya dalam Islam - Upik Nurhasanah; Hendra Hendra (Universitas Muhammadiyah Enrekang, 2023)
The problem that is the main attraction of this research is how the concept of Islamic public finance according to Abu Ubaid and how relevant it is in Islam itself. Based on these problems, an in-depth solution is needed from the perspective of Islamic public finance. And Abu Ubaid himself is one of the leading Islamic economic thinkers. The research method used in this paper is to use the narrative analysis method with literature review and literature review on the thoughts of the characters, so that it is presented in a descriptive-narrative form. By carrying out an in-depth analysis, with the data obtained, aspects of Abu Ubaid's economic thinking regarding the concept of Islamic public finance in a real situation are visible, both of which are interrelated with one another. The results obtained from this study are that the concept of public finance pioneered by Abu Ubaid focuses on the principles of justice and the distribution of wealth will be carried out fairly and evenly.